2017
DOI: 10.1111/jpc.13585
|View full text |Cite
|
Sign up to set email alerts
|

Non‐typhoidal Salmonella infections in children: Review of literature and recommendations for management

Abstract: Non-typhoidal Salmonellae are a major cause of infectious diarrhoea worldwide and can cause invasive diseases, including bacteraemia, meningitis and osteomyelitis. Young or immunocompromised children and those with underlying conditions such as sickle cell disease are particularly vulnerable to invasive disease. There has been an increase in the rate of resistant non-typhoidal Salmonella, which is associated with invasive disease and hospitalisation. The intracellular nature of non-typhoidal Salmonella protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 47 publications
(76 reference statements)
3
120
1
9
Order By: Relevance
“…Although the predominance of NTS subtypes varies from one geographical region to other, S. typhimurium, S. enteritidis and S. enterica were the three major NTS subtypes commonly isolated from gastroenteritis patients. The SalmSurv, a WHO-supported foodborne disease surveillance network study reported that S. typhimurium and S. enteritidis cause approximately 80% of all the human cases, which corroborates with our results; where S. typhimurium and S. enteritidis were the major sub types identified in our study (32). An alarming increase in the antibiotic resistance by NTS was reported elsewhere (11,12).…”
Section: Discussionsupporting
confidence: 92%
“…Although the predominance of NTS subtypes varies from one geographical region to other, S. typhimurium, S. enteritidis and S. enterica were the three major NTS subtypes commonly isolated from gastroenteritis patients. The SalmSurv, a WHO-supported foodborne disease surveillance network study reported that S. typhimurium and S. enteritidis cause approximately 80% of all the human cases, which corroborates with our results; where S. typhimurium and S. enteritidis were the major sub types identified in our study (32). An alarming increase in the antibiotic resistance by NTS was reported elsewhere (11,12).…”
Section: Discussionsupporting
confidence: 92%
“…Salmonella enterica serovar Typhimurium (S. Typhimurium) commonly causes gastroenteritis (salmonellosis) in humans and pigs [30] but human typhoid fever-like illness in mice [31]. S. Typhimurium can also cause life-threatening invasive diseases in immunocompromised individuals [32]. The intracellular environment and frequent multidrug resistance protect Salmonella enterica against extracellular antibiotics and facilitates disease relapse [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…O przynależności pałeczek Salmonella do określonych grup serologicznych decyduje natomiast budowa antygenu somatycznego a utworzone przez różne cukry proste konfiguracje chemiczne decydują o jego swoistości serologicznej. Jest to najbardziej zewnętrzna część LPS którą można uzyskać z komórki bakteryjnej różnymi metodami, w tym metodą ekstrakcji kwasem trójchlorooctowym (metoda Boivina) lub mieszaniną fenolu z wodą (metoda Westphala) (3,6,7,14).…”
Section: Materiał I Metodyunclassified